Facile Fabrication of rGO/Rutile TiO2 Nanowires as Photocatalyst for Cr(VI) Reduction. (2019) - Rahmat, S.T; Tan, W.K; Kawamura, G.; Matsuda, A.; Lockman, Z.
Abstract: Reduced Graphene Oxide (rGO) was successfully deposited on TiO2 nanowires (TNWs) via electrophoretic process. The nanowires were produced by thermal oxidation of titanium in the presence of KOH as a catalyst. It was found that the presence of KOH resulted in NWs with length up to 500 nm and average diameter of 50 nm. Nevertheless the distribution of nanowires on Ti foil varied as a function of KOH concentration. The fabricated rGO/TNWs sample was then used as photocatalyst for reduction of Cr(VI) under UV and visible light. It appears that under UV and visible light 100% reduction of 10 mg/L Cr(VI) solution was achieved within 30 and 60 minutes respectively on the rGO/TNWs sample. This could be due to the excess of electrons rGO possessed which aid in the reduction of Cr(VI) to Cr(III) as well as photogenerated electrons in TNWs under UV light.